2018
DOI: 10.1093/jn/nxy198
|View full text |Cite
|
Sign up to set email alerts
|

'Dietary Arginine Supplementation Affects Intestinal Function by Enhancing Antioxidant Capacity of a Nitric Oxide–Independent Pathway in Low-Birth-Weight Piglets

Abstract: BackgroundLow-birth-weight (LBW) neonates are susceptible to intestinal dysfunction. Furthermore, the antioxidant capacity of LBW neonates is significantly lower compared with that of normal-birth-weight (NBW) neonates both at birth and at weaning. In LBW neonates, dietary supplementation with arginine has shown beneficial effects on intestinal function.ObjectiveThe present study explored the potential mechanisms of arginine-induced protective effects against intestinal dysfunction in LBW piglets.MethodsForty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 66 publications
(87 reference statements)
1
27
0
1
Order By: Relevance
“…In this study, our results showed that MFGM supplementation (100 mg/kg BW or 200 mg/kg BW) could improve the growth performance of LBW pups from PND16 to PND21, which is consistent with the previous study [22]. The growth-promoting effects during this time zone could be explained by the increased needs of the neonates for growth but gradually decreased amount of secreted breast milk from PND14 [8, 32]. Consequently, further studies need to be done to elucidate how MFGM supplementation affects the growth performance at different ages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, our results showed that MFGM supplementation (100 mg/kg BW or 200 mg/kg BW) could improve the growth performance of LBW pups from PND16 to PND21, which is consistent with the previous study [22]. The growth-promoting effects during this time zone could be explained by the increased needs of the neonates for growth but gradually decreased amount of secreted breast milk from PND14 [8, 32]. Consequently, further studies need to be done to elucidate how MFGM supplementation affects the growth performance at different ages.…”
Section: Discussionsupporting
confidence: 91%
“…Despite advanced prenatal care for both mothers and fetuses, approximately 15% of human infants suffer from LBW worldwide [3] and approximately 15-20% of newborn piglets suffer from IUGR [4]. Neonates with LBW show impaired intestinal development, nutrient metabolism, and immune function in both human-beings [5, 6] and animal models [2, 7, 8]. Metabolic programming and the alterations in early physiological may proceed to intestinal dysfunction during the neonatal period [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IUGR piglets have been shown to be correlated with high morbidity and mortality, stunted growth, as well as poor carcass quality [1]. Great efforts have been made to minimize the negative effects of IUGR, and some investigations have shown that dietary nutrient supplementation can improve the survival and growth performance of IUGR piglets (e.g., mid-chain triglycerides [3], choline [4], arginine [5], and dimethylglycine sodium salt [6]). However, the underlying mechanisms of nutrient utilization in IUGR piglets were not well defined, and it is difficult to take effective measures to maximize the performance of IUGR piglets.…”
Section: Introductionmentioning
confidence: 99%
“…在猪生产上, 新生仔猪对精氨酸需求很高, 而 母乳中精氨酸含量很难满足仔猪生长需要. 研究显示, 低出生体重仔猪补充精氨酸显著促进了肠道发育, 并 增加了生长性能, 其作用机制可能是通过合成一氧化 氮信号分子激活机体代谢而实现的 [81] . 同时, 在早期 断奶仔猪模型上, 添加0.2%~0.8%能够有效改善生长…”
Section: 精氨酸在猪生产上被当作半必需氨基酸或条件下 必需氨基酸 除了合成蛋白质外 也是一氧化氮、肌酸unclassified